The role of knowledge, emotion, and intention in influencing students’ behaviors during COVID-19 pandemic - Masek, Alias; Paimin@Abdul Halim, Aini Nazura; Hashim, Suhaizal; Abdullah Abdullah, Nurhanim Saadah; Wan Muda, Wan Hanim Nadrah (2022)
This study aims to investigate the influence of students’ knowledge, attitude, and behavioral intention on their behaviors during the COVID-19 pandemic. A survey study was designed using an online questionnaire involving 653 respondents from the first to final-year students at a Malaysian university. A CACQ-COV instrument was designed based on the Theory of Reasoned Action (TRA) model, comprising 67 items in four constructs: students’ knowledge of the current pandemic, emotional engagement, behavioral intention, and behavioral action. The results show that the students learn most about the COVID-19 pandemic from the media and the internet platform; more than 50% of the students rated the television broadcast as the most trusted media. The mean scores of the students’ knowledge about COVID-19 facts and symptoms; emotion, intention, and action are at high levels. In addition, knowledge, emotion, and behavioral intention have significantly influenced the students’ behaviors and actions; it is noted that emotion has the greatest influence compared with knowledge and behavioral intention. The implication is that television broadcast should be the primary choice of media for carrying out future mass campaigns, in preference to social media, especially for announcing urgent matters and disseminating information related to the current issues.